Attributing Ceratocorys, Pentaplacodinium and Protoceratium to Protoceratiaceae (Dinophyceae), with descriptions of Ceratocorys malayensis sp. nov. and Pentaplacodinium usupianum sp. nov. Issue 1 (2nd January 2020) - Luo, Zhaohe; Lim, Zhen Fei; Mertens, Kenneth Neil; Krock, Bernd; Teng, Sing Tung; Tan, Toh Hii; Leaw, Chui Pin; Lim, Po Teen; Gu, Haifeng
ABSTRACT: The gonyaulacean family Protoceratiaceae is characterised by five precingular plates. It currently encompasses the type genus Ceratocorys and the fossil genus Atopodinium . Fourteen strains of Ceratocorys, Pentaplacodinium, and Protoceratium were established from Malaysian and Hawaiian waters, and their morphologies were examined using light and scanning electron microscopy. Two new species, Ceratocorys malayensis sp. nov . and Pentaplacodinium usupianum sp. nov ., were described from Malaysian waters. They share a Kofoidean plate formula of Po, Pt, 3ʹ, 1a, 6ʹʹ, 6C, 6S, 5ʹʹʹ, 1p, 1ʹʹʹʹ. Ceratocorys malayensis has a short first apical plate (1ʹ) with no direct contact with the anterior sulcal plate (Sa) whereas Pentaplacodinium usupianum had a parallelogram-shaped 1ʹ plate which often contacted the Sa plate. The genera Ceratocorys and Pentaplacodinium were emended accordingly to incorporate species bearing five or six precingular plates. The Protoceratium strain from Hawaii was morphologically similar to P. reticulatum, but differed in the lack of a ventral pore in plate 1′ and slight or lack of contact between plates 1′ and Sa, and is here designated as P . cf. reticulatum . The maximum-likelihood and Bayesian inference analyses based on SSU, LSU and ITS ribosomal DNA sequences revealed that these three genera are monophyletic and form a well-resolved group. Our results support Protoceratium and Pentaplacodinium as members of the family Protoceratiaceae, characterised by the presence of one anterior intercalary plate. Seven strains of Protoceratium cf. reticulatum, Ceratocorys malayensis and Pentaplacodinium usupianum were examined for yessotoxin production by LC-MS/MS but none produced a detectable amount of toxin.